CHARISMATIC RENEWAL AS A HELP TO CONTEMPLATION - MacNutt, Francis S (Journal of Dharma, 1992)
We have all seen how charismatic renewal has touched upon so many areas of our church life. In the late 1970's I was privileged to visit India (Bombay and Kerala State) for six weeks and therè I saw so many wonderful things going on-especially among priests. Although charismatic renewal has become especially noted for some of its more visible, spectacular manifestations, such as healing, nevertheless it also has been a less visible influence upon the contemplative prayer life of thousands of people. Certainly, the ideal of charismatic renewal is not just an explosion of Charismatic gifts, but rather the fivits of the Spirit—such as love, joy and peace- which are the goal of the gifts, and the norm of the spiritual life.